2019
DOI: 10.1371/journal.pone.0214849
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of postpartum depression by HIV status and timing of HIV diagnosis in Gauteng, South Africa

Abstract: Background Postpartum depression (PPD) is a common mental health condition that can compromise the quality of life and functional capacity of mothers and cause health and developmental problems in children born to affected mothers. Objectives We set out to measure the prevalence of PPD comparing postpartum HIV-1 infected women with pre-pregnancy HIV care experience, newly diagnosed (in latest pregnancy) HIV-1 infected women and HIV negative women, and to identify predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
1
8
1
Order By: Relevance
“…A further six studies included populations aged ≥18 years [72][73][74][75][76][77]. As such, some older adolescents (18-19 years) may have been included within the sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further six studies included populations aged ≥18 years [72][73][74][75][76][77]. As such, some older adolescents (18-19 years) may have been included within the sample.…”
Section: Discussionmentioning
confidence: 99%
“…These studies report mixed results. One study identified HIV as being associated with depressive symptoms [60] and, one reported depressive symptoms to be more prevalent amongst those participants who were known to be HIV-negative in the sample when compared to those who were living with HIV [75].…”
Section: Discussionmentioning
confidence: 99%
“…The study setting may have an effect on the correlation between HIV status and PPD. Research from high income countries predominantly report no association between HIV and PPD prevalence [ 46 48 ]. This lack of association could be explained by the type of care provided to postpartum mothers following childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers who reported having had fewer than four antenatal care visits had lower odds of screening positive for PPD in our sample. Based on literature, 38,39 we had expected that women who had more antenatal care (ANC) visits (a sign of good health-seeking behaviour) would have lower odds of being depressed due to the benefits of counselling and educational sessions about transitioning to parenthood offered during ANC, which prepares mothers for postpartum adjustment. The cross-sectional nature of the study limits us to determining temporality and thus impedes our efforts accurately to interpret this finding.…”
Section: Discussionmentioning
confidence: 99%